Social movements in tribal India. - Social Movements in Tribal India (Seminar) (2014 : Rajiv Gandhi Chair in Contemporary Studies, Barkatullah University); Chaudhary, S. N. (Shyam Nandan), 1954- (Jaipur : Rawat Publications, 2016)
Contributed articles presented at the two-day national seminar, Social Movements in Tribal India, organized by the Rajiv Gandhi Chair in Contemporary Studies, Barkatullah University, during March 21-22, 2014.
Includes bibliographical references and index.
Keywords: Social movements -- India -- Congresses; Tribes -- India -- Social conditions -- Congresses